Unexploited yield and profitability potentials of improved varietal technologies: the case of hybrid maize in Western Ethiopia - Alene, Arega D. (International Institute of Tropical Agriculture, 2007)
In view of the considerable potential for increasing food production through the generation and use of new agricultural technology, many developing countries have invested in agricultural research and extension. However, the issue of whether he intended production gains from new technologies have actually been realized by poor farmers has received little or no attention. This peruseda stochastic frontier efficiency decomposition methodology to derive the technical, allocative, and economic efficiency measures for a sample of hybrid maize producers in Western Ethiopia. The results revealed under exploitation of the potential of hybrid maize and indicated that farmers could increase production, on average, by 26% if they all adopted the recommended management practices. Furthermore, adoption of the recommended management practices coupled with optimum use of inputs, especially fertilizer, would enable the farmers to reduce production costs by an average of 39%. lncreased yields would lower per unit production cost and increase the profitability of maize production. This would in turn ensure sustainable use of improved agricultural technologies. Education, provision of input credit, and timely availability of critical inputs are positively and significantly related to the efficiency of hybrid maize production.